Condiciones laborales y estilos de vida de las enfermeras en el contexto COVID-19 - Cholán Quispe, Angie Lisbeth (2023)
The purpose of this quantitative cross-sectional correlational research was to determine if there is a relationship between the working conditions and lifestyles of nurses at the Regional Hospital of Trujillo, in the context of COVID-19, 2022 pandemic. The sample consisted of 133 nurses working at the hospital, to whom two instruments were applied: “Instrument for the evaluation of working conditions of the nursing professional” and “Lifestyle Profile Questionnaire (PEPS-I)”. The data collected were analyzed according to descriptive and inferential statistics, obtaining as results, in working conditions: an acceptable level in 60.2 % (80 nurses); while, in 39.8 % (53 nurses) a risk level was found. Regarding lifestyles, 57.9% (77 nurses) were found to be healthy and 42.1% (56 nurses) were found to be very healthy. To determine the relationship between both variables, Pearson's chi-square test was used, showing that there is a highly significant relationship. This connection is directly proportional, where p-value is equal to 0.009